Radiocarbon dates from Terra Nova Bay (Northern Victoria Land, Antarctica): conventional and calibrated ages. - BARONI, CARLO; BELLUOMINI G; BRANCA M. E; IMPROTA S; OROMBELLI G. (1991)
A list of 106 14C dates obtained from samples collected in the area of Terra Nova Bay during the 1985/86, 1986/87, 1987/88 and 1988/89 field seasons of the "Programma Nazionale di Ricerche in Antartide" (ITALIANTARTIDE) is presented. All the samples but one are Holocene in age and consist of penguin guano, penguin bones, seal bones, marine shells and lacustrine algae. The organic samples dated are connected with raised beaches and glacial sediments. They produced numerical dates for the reconstruction of the deglaciation history, relative sea-level variations and Holocene glacier fluctuations. The 14Cdates supplied by organisms that lived or fed in the circumantarctic ocean waters are depleted in 14C due to the dilution with glacial meltwater and to the upwelling of deep old oceanic water (reservoir effect). In order to correct the conventional 14C ages, it is necessary to date organisms of known age that died before the nuclear tests. Several dates of remains of penguins and seals killed during the "Heroic Era" of the Antarctic exploration have recently been supplied by several authors. In order to calibrate the 14Cdates we followed the procedure proposed by STUIVER et alii (1986 and 1987).